Scalable and sustainable blockchain architecture: advancing security, efficiency, and cross-chain interoperability - Rizuwan, Mohamad Razif Arman; Mohd Zakaria, Muhammad Khalis; Subahir, Ariff Rostam Haikqal; Tunku Mohar, Tunku Muhsin Hasni; Abdul Jamil, Ahmad Azzam; Zainuddin, Ahmad Anwar (IIUM Press, 2025)
Blockchain technology has transformed data integrity and digital transactions across various industries. Achieving optimal scalability, transparency and security is still a challenge. Barriers exist such as high energy consumption, long transaction times, and interoperability problems like the Fork problem with the consensus of decentralized node versions on software upgrades[1]. This paper proposes a novel blockchain-based architecture using layer-2 scaling techniques, energy efficient decision methods and cross-chain protocols that solves these issues [2]. This approach decreases decentralized transaction carbon footprints, boosts blockchain performance, and helps interoperability. Detailed case studies of platforms like Ethereum and Polkadot are included to demonstrate how these challenges have been tackled in practice, with specific focus on scalability and interoperability solutions. Areas such as supply chain management and finance would benefit from the newer system's improved security and reliability. It was carried out in a multi-phase manner, first evaluating the current limitations of blockchain technology. Then, a hybrid agreement model combining energy-efficient techniques with data sharing and transaction merging process was created to develop a prototype. Cross platform compatibility and performance with different transaction loads were tested in a controlled environment. The project aims to provide scalable and sustainable architecture that would be a great contribution to the blockchain community. Ciavarella explains, “For example, it provides a proof of concept for future developments in blockchain which could result in safer, more flexible and efficiency solutions across all industries.”